Cyclostomata (Bryozoa, Stenolaemata) from Rio de Janeiro State, Brazil - Ramalho, L. V.; Muricy, G.; Taylor, P. D. (Zootaxa, 2009)
Research on cyclostome bryozoan taxonomy has been neglected compared to that on cheilostomes, especially in Brazil. Between 1890 and 1979, only 25 cyclostome species have been identified from Brazil, distributed among 11 genera and seven families. This study describes eight cyclostome species (Crisia pseudosolena, Nevianipora floridana, Mecynoecia cf. delicatula, Disporella pila, Patinella sp., Crisia fragosa sp. nov., Exidmonea zagorsek sp. nov., Supercytis savii sp. nov.), including a first record of the genus Supercytis in Brazilian waters.